Calibration of Spectral Imaging Devices With Oxygenation-Controlled Phantoms: Introducing a Simple Gel-Based Hemoglobin Model - Le, V. N. Du; Manser, Myla; Gurm, Sunny; Wagner, Ben; Hayward, Joseph E.; Fang, Qiyin (Frontiers in Physics, 2019)
An optical phantom model with stable oxygen saturation (StO2) and optical properties (OPs) is the key for quick and accurate calibration of spectral imaging devices. Toward this goal, we have developed gel-based phantoms using Agarose, polystyrene microsphere, purified hemoglobin, and yeast. Theoretical values of OPs were calculated by applying Beer Lambert law and Mie theory whereas a robust fitting algorithm was used to extract StO2. Stability of OPs and StO2 in the phantoms was validated experimentally over a period of 2 weeks and the effect of pre-heating at 65°C degrees on StO2 was observed. Multi-spectral imaging (750, 780, 850, and 945 nm) of the phantoms were also performed on the FDA-approved commercial system to demonstrate the utility of the phantoms.